INSIDE AN ENGLISH LANGUAGE TEACHER EDUCATION PROGRAM IN VIETNAM: STUDENTS’ MOTIVATIONS FOR TEACHING AND THEIR INTENTIONS TO TEACH - Hong Duyen, Tran Thi; Hong, Cao Thuy (VNU Journal of Foreign Studies, 2020)
Recent years have witnessed a decrease in both the number and quality of students enrolling in English Language Teacher Education (ELTE) programs. Those ELTE graduates also tend to pursue careers other than teaching. Given the great demand for English language learning at the moment, such low motivation for teaching is undesirable. This study was thus conducted to investigate motivations for teaching of senior students at a language teacher education institution in Vietnam as well as the correlations between these motivating factors and their intentions to teach. Data was collected from 114 senior students using questionnaires, and analyzed using SPSS (version 20.0). Findings from the study suggested that (a) participants displayed a positive prospect of pursuing teaching career; (b) prior teaching and learning experience , making social contribution , and shaping future of children/adolescents were the most influential factors while fallback career , job transferability , and time for family were the least endorsed ones; (c) although teaching is perceived to be part of a respected profession that requires expert knowledge and emotional devotion, teachers are generally underpaid; (d) significant relations were observed between intrinsic career value , satisfaction with choice , social utility values , perceived ability , and prior teaching and learning experience and intentions to teach.